Panorama of Onion Production in Tillabéri, A Region of the Far West of Niger - Maman Moustapha Rabiou; Idrissa Moussa; Tchicama Mella M.; Hassimi Sadou (European Scientific Journal, ESJ, 2018)
The objective of this study was to evaluate onion production systems in four municipalities along the Niger River. A cross-sectional survey was carried out among seventy-five onion producers distributed over ten perimeters. The results obtained reveal that onion is mainly grown by women (95%). 70% of the farmers own the farmed land, 20% rent and 10% borrow. The cultivation takes place between September and March. The cultivated varieties are ‘Galmi violet’ and ‘Gothèye white’, Onions are essentially transformed into Gabou, a traditional condiment. The areas exploited are generally less than half a hectare. Irrigation relies mainly on the gravity system. NPK fertilizer and urea in combination with manure are the most commonly used. For phytosanitary treatments, producers use pesticides and/or natural products based on aqueous extract. At harvest time, the price per 100 kg bag varies from 8 000 to 15 000 FCFA (12 to 23 €) and from 40 000 to 50 000 FCFA (61 to 76 €) after four months of storage. The average production cost per hectare is 1 208 564 FCFA (1844 €) and that of the net margins 551 857 FCFA (840 €). There is a low correlation between strong investments and net margins. The major constraints faced by producers are the high cost of agricultural inputs, the rapid drying up of water points, limited access to credit, the straying of animals, the collapse of prices during the harvest period and the difficulties of farming storage and conservation.